Phenotype‐Based Isolation of Antigen‐Specific CD4+ T Cells in Autoimmunity: A Study of Celiac Disease. Issue 10 (4th February 2022) - Christophersen, Asbjørn; Dahal‐Koirala, Shiva; Chlubnová, Markéta; Jahnsen, Jørgen; Lundin, Knut E. A.; Sollid, Ludvig M.
Abstract: The pathogenic immune response in celiac disease (CeD) is orchestrated by phenotypically distinct CD4 + T cells that recognize gluten epitopes in the context of disease‐associated HLA‐DQ allotypes. Cells with the same distinct phenotype, but with elusive specificities, are increased across multiple autoimmune conditions. Here, whether sorting of T cells based on their distinct phenotype (Tphe cells) yields gluten‐reactive cells in CeD is tested. The method′s efficiency is benchmarked by parallel isolation of gluten‐reactive T cells (Ttet cells), using HLA‐DQ:gluten peptide tetramers. From gut biopsies of 12 untreated HLA‐DQ2.5 + CeD patients, Ttet + /Tphe +, Ttet − /Tphe +, and Ttet − /Tphe − cells are sorted for single‐cell T‐cell receptor (TCR)‐sequencing ( n = 8) and T‐cell clone (TCC)‐generation ( n = 5). The generated TCCs are TCR sequenced and tested for their reactivity against deamidated gluten. Gluten‐reactivity is observed in 91.2% of Ttet + /Tphe + TCCs, 65.3% of Ttet − /Tphe + TCCs and 0% of Ttet − /Tphe − TCCs. TCR sequencing reveals clonal expansion and sequence sharing across patients, features reflecting antigen‐driven responses. The feasibility to isolate antigen‐specific CD4 + T cells by the sole use of phenotypic markers in CeD outlines a potential avenue for characterizing disease‐driving CD4 + T cells in autoimmune conditions. Abstract : A distinct CD4 + T‐cell phenotype is increased across multiple autoimmune disorders. Here, a proof‐of‐concept is presented for direct isolation of antigen‐specific T cells based on this distinct phenotype of autoimmune conditions using celiac disease as a test case. The majority of isolated cells are specific to gluten, and T‐cell receptor repertoire analysis indicates antigen‐driven responses.